Reliability of Temporal Summation and Diffuse Noxious Inhibitory Control - Stuart Cathcart; Anthony H Winefield; Paul Rolan; Kurt Lushington (Pain Research and Management)
BACKGROUND: The test-retest reliability of temporal summation (TS) and diffuse noxious inhibitory control (DNIC) has not been reported to date. Establishing such reliability would support the possibility of future experimental studies examining factors affecting TS and DNIC. Similarly, the use of manual algometry to induce TS, or an occlusion cuff to induce DNIC of TS to mechanical stimuli, has not been reported to date. Such devices may offer a simpler method than current techniques for inducing TS and DNIC, affording assessment at more anatomical locations and in more varied research settings.